Method for testing flux corrosion resistance of photovoltaic cell
By comparing the moisture and heat test and EL image of the photovoltaic cell laminate, combined with silver chromate test strip detection, the problem of insufficient accuracy of the corrosion detection of flux resistance in the photovoltaic cell in the existing technology is solved, and efficient and reliable corrosion is achieved Evaluation, simulates the actual use environment, and improves detection efficiency and accuracy.
Patent Information
- Application Number
- CN202411232615.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art lacks effective flux corrosion testing methods for photovoltaic cells, and cannot accurately simulate the corrosion impact of flux on photovoltaic cells during actual use, affecting the accuracy of evaluation performance and conversion efficiency.
By preparing photovoltaic cell laminates, conducting moisture and heat tests and comparing electroglow (EL) images after initial and moisture and heat tests, using silver chromate test strips to detect whether the flux contains halogen, determine its corrosion degree, and simulate the actual use environment. Improve detection accuracy and efficiency.
It improves the accuracy and efficiency of corrosion resistance flux detection of photovoltaic cells, and can reliably evaluate the corrosion impact of flux on photovoltaic cells, save time and cost, while avoiding the problem of naked-film batteries being affected by external factors.
Smart Images

Figure CN119223853A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaic solar energy industry testing, and in particular relates to a method for testing the corrosion resistance of photovoltaic cells to solder flux. Background Art
[0002] With the rapid development of the new energy field, photovoltaic cells, as an important clean energy conversion device, play an increasingly important role in the field of solar power generation. In the production process of photovoltaic cell components, flux is an auxiliary material used in the welding process. Its main function is to remove oxides and impurities on the welding surface and improve the welding quality. During welding, the flux will contact the surface of the cell, and the flux usually contains components that corrode the cell. The commonly used organic flux, inorganic flux and rosin resin flux in the industry will cause different degrees of corrosion to the cell when used in actual applications; halogen hydrides are common components in flux, such as hydrofluoric acid, hydrochloric acid, hydrobromic acid and hydroiodide, etc. Hydrohalic acid will cause obvious corrosion. In the future, with the trend of environmental protection, flux will develop in the direction of lead-free and halogen-free.
[0003] The corrosion caused by flux is manifested as spots on the surface of the cell, peeling of the oxide film or decreased conductivity. In particular, corrosion is more likely to be aggravated under hot and humid conditions, which in turn affects the conversion efficiency and long-term stability of photovoltaic cells. Therefore, the ability of photovoltaic cells to resist flux corrosion will become one of the important indicators for evaluating performance. However, there is currently a lack of relevant standards for testing methods for photovoltaic cell resistance to flux corrosion, and research methods in the industry are still lacking. The existing technical achievements and patents involving testing methods for photovoltaic cell resistance to flux also have the problem of being unable to simulate the corrosion problems that occur during actual use.
[0004] Therefore, it is urgent to provide a method for detecting the resistance of photovoltaic cells to flux corrosion and a method for simulating the effect of flux on the performance of photovoltaic cells. Summary of the invention
[0005] In order to overcome the technical problems existing in the prior art, the present invention provides a testing method for the corrosion resistance of photovoltaic cells by flux, which not only improves the detection efficiency, but also has high detection coverage and high accuracy.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for testing the corrosion resistance of photovoltaic cells to solder flux comprises the following steps:
[0008] Preparation of photovoltaic cell laminates and testing of initial EL;
[0009] performing a damp heat test on the photovoltaic cell laminate;
[0010] Testing the photovoltaic cell laminate EL after the damp heat test;
[0011] The solder flux is tested for halogen content and the extent of solder flux corrosion is determined by comparing the initial EL image of the photovoltaic cell laminate with the EL image after the damp heat test.
[0012] Furthermore, the preparation of the photovoltaic cell laminate comprises the following steps:
[0013] Prepare multiple defect-free battery cells, connect the circuits using interconnecting bars and bus bars, and lead out the electrodes;
[0014] Apply flux on the battery cells and make markings;
[0015] Paste silver chromate test paper on the area where the flux is applied;
[0016] Photovoltaic cell laminates are manufactured in the order of stacking glass, adhesive film, cell sheet, adhesive film and backplane.
[0017] In the specific implementation process, the appropriate size and quantity are selected according to the size of the photovoltaic cell laminate, preferably 1 to 4 pieces; when there are multiple cell sheets, they are all located between the adhesive films.
[0018] In the specific implementation process, the flux is applied and then heat-dried, which can be done by using a hot air gun, infrared heating, flux drying machine, etc.
[0019] Furthermore, the damp heat test conditions are: temperature 100-150° C., humidity 88-100%, and time 12-192 hours, wherein the damp heat test can be performed in a temperature and humidity test chamber.
[0020] Preferably, the temperature is 106°C, 110°C, 116°C, 121°C, 126°C, 130°C, 135°C, 140°C, 145°C or 150°C; preferably, the humidity is 88%, 90%, 92%, 94%, 96%, 98% or 100%; and the time may be 12h, 24h, 48h, 96h, 120h, 144h, 168h or 192h.
[0021] Furthermore, the types of the cell include TOPCon (tunneling oxide passivated contact cell), PERC (passivated emitter and back cell), xbc (cross back contact solar cell) or HJT (crystalline silicon heterojunction cell), and the cell specifications are rectangular with a side length of 50 to 210 mm; preferably, the side length is 70 to 180 mm, and more preferably 80 to 160 mm.
[0022] Furthermore, the area where the soldering flux is applied is located in the main grid, fine grid and coating area of the cell, and the total coverage area of the area where the soldering flux is applied accounts for 30-50% of the cell, preferably 35-45%;
[0023] The arrangement direction of the main grid and the fine grid is not limited, for example, the two are perpendicular to each other, cross at a small angle, etc., and the area on the solar cell in the coating area is not covered by the main grid and the fine grid.
[0024] Furthermore, the area for applying flux is 1 to 10, preferably 2 to 5; the amount of flux used is 1 to 5 mL per area, for example, 1 mL, 2 mL, 3 mL, 4 mL, or 5 mL; in the specific implementation process, multiple areas for applying flux ensure that the amount of flux used in each area is consistent.
[0025] The brushing tools include a flux pen, a spray needle, and a soft brush, preferably a soft brush. In the specific implementation process, the flux is quantitatively dropped on the area where the flux is to be brushed and evenly applied.
[0026] Furthermore, the types of flux applied to the surface of the cell include various types of organic flux, inorganic flux or rosin resin flux used in production. Usually, the flux used for photovoltaic welding often contains halogen activators as one of the ingredients. When the halogen ions react with the silver ions on the silver chromate test paper, silver halide precipitation is generated, and its color is white or yellow, which can be used to determine that the flux contains halogen.
[0027] Furthermore, the adhesive film includes POE or PVB, and the adhesive film does not contain acetic acid.
[0028] Furthermore, the silver chromate test paper is within the area where the soldering flux is applied.
[0029] Furthermore, the photovoltaic cell laminate is a rectangle with a side length of 300 to 1000 mm; preferably 300*300mm, 350*400mm, 400*400mm, 500*500mm, 600*600mm, 650*700mm, 800*800mm, 900*900mm, 850*950mm or 850*1000mm.
[0030] Further, the testing whether the soldering flux contains halogen and determining the corrosion degree of the soldering flux by comparing the initial EL image of the photovoltaic cell laminate and the EL image after the wet heat test includes:
[0031] Use silver chromate test paper to test whether the flux contains halogen;
[0032] The initial EL image and the EL image after the humidity and heat test are compared, and the degree of corrosion of the soldering flux is determined according to the comparison result, including: the corrosion resistance of the soldering flux is inversely proportional to the difference between the initial EL image and the EL image after the humidity and heat test; the degree of corrosion of the soldering flux is directly proportional to the difference between the initial EL image and the EL image after the humidity and heat test;
[0033] Wherein, the difference between the initial EL image and the EL image after the damp heat test is characterized by the degree of blackening of the EL image after the damp heat test;
[0034] The comparison includes human eye comparison or computer vision and image processing using an image comparison device; the human eye comparison can simply and quickly determine the degree of corrosion of the flux; the image comparison device can calculate the area of the blackened area, quantify the blackening degree value, complete the blackening degree characterization, and accurately display the degree of corrosion of the flux.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The test method for the corrosion resistance of photovoltaic cells by flux proposed in the present invention is to make a simple photovoltaic cell laminate and test the initial EL of the laminate, conduct a damp heat test and test the EL after the damp heat test, and observe the changes of the silver chromate test paper in the laminate to determine whether the halogen-containing flux causes corrosion to the photovoltaic cell. In addition, by comparing the EL images before and after the damp heat test, the corrosion resistance of the flux can be determined. On the one hand, by making a photovoltaic laminate, the present invention simulates the complete state of the photovoltaic module in actual use, provides reliable detection accuracy for the detection of flux corrosion, avoids the problem of conventional methods such as the use of bare chip cells being affected by external factors, and the small size of the laminate can reduce consumables and save costs; on the other hand, the flux corrosion resistance test method proposed in the present invention is simple and reliable, and the corrosion rate is accelerated by the temperature and humidity environment, saving time and cost for the study of flux corrosion.
[0037] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by implementing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A flow chart of the test method for the corrosion resistance of photovoltaic cells to solder flux;
[0039] Figure 2 is the EL test image of Example 1;
[0040] Figure 3This is the EL test image of Example 2;
[0041] Figure 4 This is the EL test image of Comparative Example 1. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the implementation scheme of the present application will be described in detail below in conjunction with specific examples. The technical terms and scientific terms used in the present invention have the meanings generally understood by ordinary technicians in the technical field to which the present invention belongs, without other definitions. Without departing from the concept of the present invention, those skilled in the art may make various improvements and changes to the specific implementation methods of the present invention specification, which all belong to the protection scope of the present invention.
[0043] Example 1
[0044] A test method for the corrosion resistance of photovoltaic cells to flux, see Figure 1 The flow chart specifically includes the following steps:
[0045] S1. Prepare photovoltaic cell laminate and test initial EL;
[0046] The preparation of the photovoltaic cell laminate comprises the following steps:
[0047] (1) Select several defect-free XBC cells for backup. The size of the cell is 166mm*83mm. Take out two cells, use interconnection strips to connect the positive and negative electrodes of the cells, and then use busbars to lead out the electrodes;
[0048] (2) Use a 1.5 cm wide soft brush to apply 2 mL of solder to four areas on the surface of the cell. Mark the areas accordingly. The solder flux is Cosda FD-309 lead-free and halogen-free solder flux.
[0049] (3) Use a hot air gun to blow for 5 to 10 seconds, and then paste the silver chromate test paper on the battery cell coating area after the flux is dried. (The time for hot air gun blowing is based on the complete drying of the flux. Natural drying is also possible.)
[0050] (4) Pre-prepare a laminate with a size of 350*350 mm, and make a photovoltaic cell laminate sample 1# according to the stacking order of glass, POE film, battery cell (two cells are located on the same layer between the films), POE film, and backplane.
[0051] The initial EL image of the photovoltaic cell laminate was tested using an EL tester. Figure 2 .
[0052] S2. performing a damp heat test on the photovoltaic cell laminate simulating actual use conditions;
[0053] Sample 1# was placed in a temperature and humidity test box at a temperature of 121°C and a humidity of 100% and tested for 48h, 120h, and 192h.
[0054] S3, EL images of photovoltaic cell laminates after 48h, 120h, and 192h damp heat tests, see Figure 2 ;
[0055] S4. Observe the silver chromate test paper in the photovoltaic cell laminate to determine whether the photovoltaic cell is corroded by flux, and determine the degree of corrosion by comparing the initial EL of the photovoltaic cell laminate and the EL after the wet heat test.
[0056] The color of the silver chromate test paper in sample 1# did not change, indicating that the flux does not contain halogen. Figure 2 Taking the initial EL image of sample 1# as a comparison, at 48h, slight black lines can be seen in the flux-coated area around the main grid of sample 1#, at 120h, obvious black corrosion bands can be seen around the main grid of sample 1#, and at 192h, continuous large-area black corrosion areas can be seen around the main grid and the fine grid of sample 1#, as well as black spot-like corrosion areas in the coating area.
[0057] Example 2
[0058] The difference from Example 1 is that the soldering flux used is a halogen-containing soldering flux, and a photovoltaic cell laminate sample 2# is prepared.
[0059] Among them, the color of the silver chromate test paper changes to yellow; the test results are shown in Figure 3 Taking the initial EL image of sample 2# as a comparison, intermittent black spots can be seen in the flux-coated area around the main grid of sample 2# at 48h, obvious black corrosion bands can be seen around the main grid of sample 2# at 120h, and continuous large-area black corrosion areas can be seen around the main grid of sample 2# and the fine grid at 192h.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that no soldering flux is used to prepare photovoltaic cell laminate sample 0#.
[0062] Among them, the silver chromate test paper does not change color, indicating that no halogen is detected; the test results are shown in Figure 4 , among which no black corrosion was shown at 48h, 120h and 192h.
[0063] The test results of Examples 1 and 2 show that there is no abnormality in the EL of the cell in the initial stage when the flux with different solid contents is applied. After 48h, 120h, and 192h of wet heat, the cell performance results all show blackening phenomenon. The blackening phenomenon intensifies with the extension of time and is distributed on the main grid and both sides, and diffuses to the fine grid. In addition, the samples coated with halogen-containing flux in Example 2 show more serious blackening as the test time progresses, indicating that the corrosiveness of the halogen-containing flux is more serious.
[0064] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for testing the corrosion resistance of photovoltaic cells to solder flux, characterized in that: The following steps are involved: Preparation of photovoltaic cell laminates and testing of initial EL; performing a damp heat test on the photovoltaic cell laminate; Testing the photovoltaic cell laminate EL after the damp heat test; The solder flux is tested for halogen content and the extent of solder flux corrosion is determined by comparing the initial EL image of the photovoltaic cell laminate with the EL image after the damp heat test.
2. The method for testing the corrosion resistance of photovoltaic cells by flux according to claim 1, characterized in that: The preparation of the photovoltaic cell laminate comprises the following steps: Prepare multiple defect-free battery sheets and connect the circuits using interconnect bars and bus bars; Apply flux on the battery cells and make markings; Paste silver chromate test paper on the area where the flux is applied; Photovoltaic cell laminates are manufactured in the order of stacking glass, adhesive film, cell sheet, adhesive film and backplane.
3. The method for testing the corrosion resistance of photovoltaic cells by flux according to claim 1, characterized in that: The damp heat test conditions are: temperature 100-150° C., humidity 88-100%, and time 12-192 h.
4. A method for testing the corrosion resistance of photovoltaic cells by flux according to claim 2, characterized in that: The types of cells include TOPCon, PERC, xBC or HJT.
5. A method for testing the corrosion resistance of photovoltaic cells to solder flux according to claim 2, characterized in that: The area where the soldering flux is applied is located in the main grid, fine grid and coating area of the battery cell, and the total coverage area of the area where the soldering flux is applied accounts for 30-50% of the battery cell.
6. A method for testing the corrosion resistance of photovoltaic cells to solder flux according to claim 5, characterized in that: The area for applying the soldering flux is 1-10 places, and the amount of the soldering flux used is 1-5 mL per place.
7. A method for testing the corrosion resistance of photovoltaic cells to solder flux according to claim 2, characterized in that: The adhesive film includes POE or PVB.
8. A method for testing the corrosion resistance of photovoltaic cells to solder flux according to claim 2, characterized in that: The silver chromate test paper is pasted in the painting area.
9. A method for testing the corrosion resistance of photovoltaic cells to solder flux according to claim 2, characterized in that: The photovoltaic cell laminate is a rectangle with a side length of 300 to 1000 mm.
10. A method for testing the corrosion resistance of photovoltaic cells to solder flux according to claim 1, characterized in that: The method of testing whether the soldering flux contains halogen and determining the corrosion degree of the soldering flux by comparing the initial EL image of the photovoltaic cell laminate and the EL image after the wet heat test includes: Use silver chromate test paper to test whether the flux contains halogen; The initial EL image and the EL image after the damp heat test are compared, and the difference between the initial EL image and the EL image after the damp heat test is characterized by the blackening degree of the EL image after the damp heat test.
